Semiconductor Quantum Dots‐Embedded Inorganic Glasses: Fabrication, Luminescent Properties, and Potential Applications. Issue 21 (7th August 2019) - Xia, Mengling; Luo, Jiajun; Chen, Chao; Liu, Huan; Tang, Jiang
Abstract: Quantum dots (QDs)‐embedded inorganic glasses combine the outstanding luminescent properties of QDs with the chemical, mechanical, and thermal stability of glasses, overcoming the instability bottleneck of QDs and facilitating their wide and endurable applications such as nonlinear optical devices, light emission, and signal amplification in the fiber‐optic communication system. Typical QDs incorporated into glasses include IIB‐VIA (e.g., ZnO, CdSe), IVB‐VIA (e.g., PbS), and halide perovskite (CsPbBr3, et al.) QDs. Here, the preparation methods and growth kinetics of QDs in glasses are first discussed, followed by the summary of the optical properties and application explorations of IIB‐VIA, IVB‐VIA, and halide perovskite QDs‐embedded glasses. Finally, research directions to overcome the major challenges associated with these glasses for ultimate applications are proposed. Abstract : Quantum dots (QDs)‐embedded glasses combine the outstanding luminescent properties of QDs with the chemical, mechanical, and thermal stability of inorganic glasses, overcoming the instability bottleneck of QDs and facilitating their wide and endurable applications such as nonlinear optical devices, light emission, and signal amplification in the fiber‐optic communication system.